Uncemented Primary Press-Fit Total Hip Arthroplasty: A 3 to 6 Years of Experience - S Vidyadhara; SK Rao (Journal of Orthopaedic Surgery, 2007)
Purpose. To analyse the 3 to 6 years' clinicoradiological outcome of 45 uncemented total hip arthroplasties performed in 37 patients using cementless Spotorno stem and St Nabor cup. Methods. The main indications for surgery were avascular necrosis of the femoral head and rheumatoid arthritis. Younger patients with good bone quality and a trumpet-shaped femur were eligible. A single surgeon performed all the operations using a posterolateral approach. Patients were reviewed at 6 weeks, 3 months, 6 months, and yearly thereafter. The clinical status was recorded using the Harris Hip Score. All radiographs were analysed by 2 independent blinded observers on 2 separate occasions. Results. The mean follow-up period was 49 months and the mean Harris Hip Score at the latest follow-up was 94. Osseointegration in the form of trabeculae running from the endosteum to the prosthesis surface along with tropism of the calcar was evident in 73% of the hips. None of the remaining hips showed any continuous radio-opaque lines suggestive of a lack of bone ongrowth. Patients with endosteal condensation had better Harris Hip Scores. Intra-operative stability of the implants could fairly predict outcome. Conclusion. Initial clinicoradiological results of uncemented total hip arthroplasty are promising in younger patients with good bone quality and a trumpet-shaped femur.